A method for preparing low-melting-point antibacterial fiber based on zinc oxide particles

By adding zinc oxide nanoparticles during low melting point polymerization, low melting point antibacterial fibers with a skin core structure are prepared, which solves the problems of existing fiber failure at high temperature and high antibacterial agent costs, and achieves excellent antibacterial properties and high temperature resistance sex.

CN116356451BActive Publication Date: 2025-02-07ZHEJIANG HENGYI PETROCHEMICAL RES INST CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310081166.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-08
Publication Date
2025-02-07
Estimated Expiration
2043-02-08

AI Technical Summary

Technical Problem

The existing low-melting point antibacterial fibers may fail under high temperature treatment, and the antibacterial agent costs are high, and there are compatibility and binding problems in processing.

Method used

Using the preparation method of low-melting point antibacterial fiber based on zinc oxide particles, an antibacterial dispersion is prepared by mixing zinc oxide powder with organic solvents, and zinc oxide nanoparticles are added during the low-melting point polymerization process to form low-melting point antibacterial fibers with a skin core structure. .

Benefits of technology

It realizes the resistance and durability of fibers under high temperature treatment, reduces the use of antibacterial agents, improves antibacterial and binding properties, and meets the requirements for taking sports fabrics and uppers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004067447970000071
    Figure BDA0004067447970000071
Patent Text Reader

Abstract

The invention relates to the technical field of low-melting antibacterial fiber preparation, and discloses a method for preparing low-melting antibacterial fiber based on zinc oxide particles, comprising the following steps: (1) adding zinc oxide powder to an organic solvent to prepare an antibacterial dispersion; (2) mixing terephthalic acid, ethylene glycol, butanediol, the antibacterial dispersion and a catalyst for pulping, and then heating to carry out an esterification reaction; after the reaction is completed, adding PEG to carry out a polycondensation reaction to prepare an antibacterial low-melting slice; (3) pre-crystallizing and segmentally drying the antibacterial low-melting slice in sequence, using the slice as a skin layer and conventional PET slice as a core layer, and melt spinning to prepare a low-melting antibacterial fiber with a skin-core structure. The invention adds zinc oxide nanoparticles during the low-melting polymerization process, so that the fiber has excellent antibacterial properties, better bonding and compatibility, and improves the antibacterial properties without damaging the original performance advantages of the fiber.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of preparation of low-melting-point antibacterial fibers, and in particular to a method for preparing low-melting-point antibacterial fibers based on zinc oxide particles. Background Art

[0002] In recent years, with the innovation and development of petroleum refining technology, the market share of synthetic fibers has gradually increased, and with the continuous improvement of people's requirements for the performance of chemical fibers, the proportion of various functional fibers has also increased year by year. Low-melting-point antibacterial fiber is a new type of differentiated fiber. On the basis of conventional low-melting-point fiber, it has added antibacterial properties, making the application range of this fiber wider, especially in the application of sports fabrics, it has both good adhesion and excellent antibacterial properties.

[0003] At present, the commonly used antibacterial agent in synthetic fibers is silver ion antibacterial agent. The main mechanism is that the surfactant of microorganisms is negatively charged, while the dissolved silver ions are positively charged. Under the action of Coulomb force, the two are easily attracted to each other. Silver ions are absorbed to the surface of microorganisms and enter the cells. When a certain amount of silver ions accumulate in the surfactant of microbial cells, it will destroy its electrolytic balance, causing the cell wall to be damaged and die. On the other hand, silver ions will break through the cell wall, enter the interior of the microorganism, contact proteins and nucleic acids, produce chemical reactions, denature proteins, reduce the activity of proteases, affect the metabolism and respiratory function of cells, thereby inhibiting the growth and reproduction of microorganisms and causing their death. However, in general, the cost of silver is relatively high, so a lower-cost antibacterial agent is needed, and after the antibacterial agent is added to the fiber, it can have better binding and compatibility, while improving the antibacterial property, it does not damage the original performance advantages of the fiber.

[0004] The Chinese invention patent with publication number CN105200550A discloses a low-melting-point antibacterial shaped polyester monofilament and a processing method thereof, wherein the mass percentage of the raw material components is: 1-5% antibacterial agent, 5-25% pigment, 0.5-1% dispersant, 0.5-1% antioxidant, and the balance is low-melting-point polyester chips. The antibacterial agent is a skin-core structure, the skin layer is chitin material, and the core layer is a preliminary antibacterial function modifier. However, the skin layer of the antibacterial material is chitin, which may fail at high temperatures during processing and lose its antibacterial effect. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a method for preparing a low-melting-point antibacterial fiber based on zinc oxide particles. The prepared low-melting-point polyester fiber not only has excellent antibacterial properties, but also has good mechanical properties and wearing comfort, which meets the current wearing requirements of sports fabrics and sports shoe uppers.

[0006] The purpose of the present invention is achieved through the following technical solution: The present invention provides a method for preparing a low-melting-point antibacterial fiber based on zinc oxide particles, comprising the following steps:

[0007] (1) adding zinc oxide powder into an organic solvent to prepare an antibacterial dispersion;

[0008] (2) mixing terephthalic acid, ethylene glycol, butanediol, an antibacterial dispersion and a catalyst, and then heating to carry out an esterification reaction; after the reaction is completed, adding PEG to carry out a polycondensation reaction to obtain an antibacterial low-melting-point slice;

[0009] (3) The antibacterial low-melting-point slices are pre-crystallized and dried in sections, and then melt-spun using the slices as the skin layer and conventional PET slices as the core layer to obtain a low-melting-point antibacterial fiber with a skin-core structure.

[0010] Compared with conventional low-melting polyester, the low-melting fiber of the present invention has antibacterial properties, excellent adhesion and good wearing comfort. The low-melting cortical structure can be used as an adhesive under high-temperature treatment, and the core layer provides strength, which meets the current wearing requirements of sports fabrics and sports shoe uppers. Compared with conventional antibacterial fibers, the antibacterial agent zinc oxide only exists in the cortex, which ensures antibacterial properties while reducing the usage, further reducing costs.

[0011] In addition, the monomer composition of the low melting point polyester in the present invention is obtained through screening, and butanediol can destroy the regularity of the polyester macromolecular structure, greatly increasing the proportion of its amorphous region, which is conducive to the zinc oxide antibacterial agent being well dispersed in the polyester macromolecular chain, having good compatibility and bonding, and allowing the polyester to have a higher degree of crystallinity, thereby having better spinnability. After the esterification reaction is completed, the addition of PEG helps to destroy the symmetry of the molecular chain, increase flexibility, reduce the melting point and improve crystallization, and then carry out a polycondensation reaction to obtain an antibacterial low melting point slice with good spinnability.

[0012] Preferably, in step (1), the method for preparing the antibacterial dispersion comprises: adding zinc oxide powder to ethylene glycol and stirring thoroughly until there is no powder, then adding a stabilizer and grinding until the particle size is less than 1 um to obtain an antibacterial dispersion; the mass ratio of the zinc oxide powder to the ethylene glycol is 1:2; the mass ratio of the stabilizer to the zinc oxide powder is 5:100.

[0013] Preferably, in step (2), the alcohol-acid ratio of terephthalic acid, ethylene glycol and butanediol is 1:1.2-1.4, wherein the mass fraction of butanediol in alcohol is 10-12%.

[0014] The proportion of butanediol added will affect the melting point and processability of polyester, as well as the regular structure of the polyester molecular chain and the proportion of the amorphous region. If too much is added and the crystallinity is low, it will not be conducive to spinning to obtain low-melting-point fibers with better performance.

[0015] Preferably, in step (2), the amount of the antibacterial dispersion added is 8000-24000ppm of the antibacterial low melting point slices, the mass of zinc oxide in the antibacterial low melting point slices is 4000-12000ppm; the amount of the catalyst added is 350-500ppm of the mass of the antibacterial low melting point slices.

[0016] The addition of zinc oxide can lower the crystallization temperature of polyester and affect the spinnability. Therefore, the amount of zinc oxide added needs to be controlled and it is not advisable to add too much.

[0017] Preferably, in step (2), the molecular weight of the PEG is 2000-6000; the amount of the PEG added is 1-3% of the mass of the antibacterial low-melting-point slice.

[0018] Preferably, in step (2), the temperature of the esterification reaction is 220-240°C; and the polycondensation reaction is: after vacuuming for 1 hour, the negative pressure is evacuated to -0.1 MPa, and the temperature is controlled to 270-275°C.

[0019] Preferably, in step (3), the pre-crystallization is: under a vacuum pressure of -0.1 MPa, the temperature is 50°C, and the pre-crystallization is performed for 3 to 5 hours; the staged drying is: first heating to 60°C and drying for 5 to 7 hours, then heating to 70°C and drying for 5 to 7 hours, and finally heating to 80°C and drying for 8 to 9 hours, until the moisture content is below 20 ppm.

[0020] The addition of butanediol to the low-melting-point polyester increases the proportion of amorphous regions. The pre-crystallization process can improve the crystallinity, avoid agglomeration of slices during the drying process, and improve spinnability.

[0021] Preferably, in step (3), during the melt spinning, the skin layer accounts for 30-40% of the total mass of the melt, the spinning manifold temperature of the skin layer is 225-227°C, and the spinning manifold temperature of the core layer is 288-290°C.

[0022] Preferably, in step (3), the filament bundle formed after melt spinning is sequentially subjected to side-blowing cooling, oiling, drawing, and winding to obtain a low-melting-point antibacterial fiber with a core-sheath structure.

[0023] Preferably, the temperature of the side blowing air is 20-25°C, the humidity is 70-75%, and the speed is 0.40-0.55 m / s; the temperature of the first hot roller for stretching is 40-55°C, the temperature of the second hot roller is 95-110°C, and the stretching ratio is 3.0-3.5; the winding speed is 3400-3600 m / min.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] (1) By adding zinc oxide nanoparticles during the low-melting point polymerization process, the fiber has excellent antibacterial properties, and the antibacterial agent and the fiber matrix have good binding and compatibility, which improves the antibacterial properties without damaging the original performance advantages of the fiber;

[0026] (2) The low-melting-point antibacterial fiber has better high-temperature resistance and durability, and thus better processability, which enables it to use lower energy consumption in hot-melt processing, thus effectively saving energy and costs;

[0027] (3) The hot melt method is more environmentally friendly and green than chemical bonding, and is environmentally friendly. It has no side effects on users and is healthier. DETAILED DESCRIPTION

[0028] The technical solution of the present invention is described below with specific embodiments, but the protection scope of the present invention is not limited thereto:

[0029] Example 1

[0030] (1) ZnO powder is dissolved in ethylene glycol twice its weight and stirred until there is no powder. The solution is then added to a grinder and ground. A polyvinyl pyrrole stabilizer accounting for 5% of the weight of the ZnO powder is added and ground until the particle size is less than 1 μm to obtain an antibacterial dispersion.

[0031] (2) Terephthalic acid (PTA), ethylene glycol (EG), and butanediol (BDO) were added to the reactor to make the alcohol-acid ratio of 1:1.2, wherein the butanediol (BDO) accounted for 10% of the alcohol mass fraction, and antibacterial dispersion and antimony trioxide were added at the same time, wherein the amount of antimony trioxide added was 400ppm of the mass of the antibacterial low-melting-point slices, and the mass of zinc oxide in the antibacterial low-melting-point slices was 10000ppm. After beating for 20 minutes, three passes and three releases were performed; the reactor temperature was raised to 230°C, and the esterification stage was completed after the water was completely discharged; then, after stirring at normal pressure for 20 minutes, liquid PEG2000 accounting for 3% of the mass of the antibacterial low-melting-point slices was added, and after stirring for 15 minutes, vacuum was drawn, and after 1 hour, the vacuum was drawn to -0.1MPa, and the temperature was controlled at 272°C. After polycondensation reaction, the final antibacterial low-melting-point slices (with a characteristic viscosity of 0.71dl / g and a melting point of 180°C) were obtained.

[0032] (3) The antibacterial low melting point chips were pre-crystallized at a vacuum degree of -0.1 MPa and a temperature of 50°C for 4 h, and then dried in stages. The temperature was raised to 60°C for drying for 6 h, then raised to 70°C for drying for 6 h, and finally raised to 80°C for drying for 8 h, until the moisture content was below 20 ppm. The spinning process adopted a spinneret with a skin-core structure, in which the dried antibacterial low melting point chips were the skin layer and the conventional PET chips were the core layer, with a mass ratio of 30:70. The screw temperature of the skin spinning was 225°C / 230°C / 230°C / 230°C, and the spinning manifold temperature was 225°C. The screw temperature of the core spinning was 285°C / 290°C / 290°C / 290°C, and the spinning manifold temperature was 288°C.

[0033] The two melts form a fine flow at the core-sheath spinneret. The filament bundle formed after spinning is first cooled by side air blowing. The side air temperature is 20°C, the side air speed is 0.50m / s, and the side air humidity is 73%. Then it is oiled and stretched in sequence. The temperature of the first hot roller is 50°C, the temperature of the second hot roller is 100°C, and the stretching ratio is 3.0. Finally, it is wound at a speed of 3500m / min to obtain a low-melting-point antibacterial fiber with a core-sheath structure.

[0034] Example 2

[0035] (1) ZnO powder is dissolved in ethylene glycol twice its weight and stirred until there is no powder. The solution is then added to a grinder and ground. A polyvinyl pyrrole stabilizer accounting for 5% of the weight of the ZnO powder is added and ground until the particle size is less than 1 μm to obtain an antibacterial dispersion.

[0036] (2) Terephthalic acid (PTA), ethylene glycol (EG), and butanediol (BDO) were added to the reactor to make the alcohol-acid ratio of 1:1.3, wherein the mass fraction of butanediol (BDO) accounted for 11% of the alcohol. At the same time, antibacterial dispersion and antimony trioxide were added, wherein the amount of antimony trioxide added was 400ppm of the mass of the antibacterial low-melting-point slices, and the mass of zinc oxide in the antibacterial low-melting-point slices was 5000ppm. After beating for 20 minutes, three passes and three releases were performed; the reactor temperature was raised to 230°C, and the esterification stage was completed after the water was completely discharged; then, after stirring at normal pressure for 20 minutes, liquid PEG2000 accounting for 3% of the mass of the antibacterial low-melting-point slices was added, and after stirring for 15 minutes, vacuum was evacuated and the temperature was reduced to -0.1MPa after 1 hour. The temperature was controlled at 272°C, and after polycondensation reaction, the final antibacterial low-melting-point slices (with a characteristic viscosity of 0.75dl / g and a melting point of 180°C) were obtained.

[0037] (3) The antibacterial low melting point chips were pre-crystallized at a vacuum degree of -0.1 MPa and a temperature of 50°C for 3 h, and then dried in stages. The temperature was raised to 60°C for drying for 5 h, then raised to 70°C for drying for 5 h, and finally raised to 80°C for drying for 8 h, until the moisture content was below 20 ppm. The spinning process adopted a spinneret with a skin-core structure, in which the dried antibacterial low melting point chips were the skin layer and the conventional PET chips were the core layer, with a mass ratio of 35:65. The screw temperature of the skin spinning was 225°C / 230°C / 230°C / 230°C, and the spinning manifold temperature was 225°C. The screw temperature of the core spinning was 285°C / 290°C / 290°C / 290°C, and the spinning manifold temperature was 288°C.

[0038] The two melts form a fine flow at the core-sheath spinneret. The filament bundle formed after spinning is first cooled by side-blowing, with the side-blowing temperature being 20°C, the side-blowing speed being 0.50 m / s, and the side-blowing humidity being 73%. Then, the filament bundle is oiled and stretched in sequence, with the temperature of the first hot roller being 50°C, the temperature of the second hot roller being 100°C, and the stretching ratio being 2.8. Finally, the filament bundle is wound at a speed of 4000 m / min to obtain a low-melting-point antibacterial fiber with a core-sheath structure.

[0039] Example 3

[0040] (1) ZnO powder is dissolved in ethylene glycol twice its weight and stirred until there is no powder. The solution is then added to a grinder and ground. A polyvinyl pyrrole stabilizer accounting for 5% of the weight of the ZnO powder is added and ground until the particle size is less than 1 μm to obtain an antibacterial dispersion.

[0041] (2) Terephthalic acid (PTA), ethylene glycol (EG), and butanediol (BDO) were added to the reactor to make the alcohol-acid ratio of 1:1.3, wherein the butanediol (BDO) accounted for 12% of the alcohol mass fraction, and antibacterial dispersion and antimony trioxide were added at the same time, wherein the amount of antimony trioxide added was 450ppm of the mass of the antibacterial low-melting-point slices, and the mass of zinc oxide in the antibacterial low-melting-point slices was 5000ppm. After beating for 20 minutes, three passes and three releases were performed; the reactor temperature was raised to 230°C, and the esterification stage was completed after the water was completely discharged; then, after stirring at normal pressure for 20 minutes, liquid PEG2000 accounting for 3% of the mass of the antibacterial low-melting-point slices was added, and after stirring for 15 minutes, vacuum was drawn, and after 1 hour, the vacuum was drawn to -0.1MPa, and the temperature was controlled at 272°C. After polycondensation reaction, the final antibacterial low-melting-point slices (with a characteristic viscosity of 0.75dl / g and a melting point of 180°C) were obtained.

[0042] (3) The antibacterial low melting point chips were pre-crystallized at a vacuum degree of -0.1 MPa and a temperature of 50°C for 5 h, and then dried in stages. The temperature was raised to 60°C for drying for 7 h, then raised to 70°C for drying for 7 h, and finally raised to 80°C for drying for 8 h, until the moisture content was below 20 ppm. The spinning process adopted a spinneret with a skin-core structure, in which the dried antibacterial low melting point chips were the skin layer and the conventional PET chips were the core layer, with a mass ratio of 35:65. The screw temperature of the skin spinning was 225°C / 230°C / 230°C / 230°C, and the spinning box temperature was 227°C. The screw temperature of the core spinning was 285°C / 290°C / 290°C / 290°C, and the spinning box temperature was 290°C.

[0043] The two melts form a fine flow at the core-sheath spinneret. The filament bundle formed after spinning is first cooled by side-blowing, with the side-blowing temperature being 20°C, the side-blowing speed being 0.50 m / s, and the side-blowing humidity being 73%. Then, the filament bundle is oiled and stretched in sequence, with the temperature of the first hot roller being 50°C, the temperature of the second hot roller being 100°C, and the stretching ratio being 2.8. Finally, the filament bundle is wound at a speed of 4000 m / min to obtain a low-melting-point antibacterial fiber with a core-sheath structure.

[0044] Comparative Example 1

[0045] The difference from Example 1 is that the antibacterial dispersion is added after the esterification reaction.

[0046] (1) ZnO powder is dissolved in ethylene glycol twice its weight and stirred until there is no powder. The solution is then added to a grinder and ground. A polyvinyl pyrrole stabilizer accounting for 5% of the weight of the ZnO powder is added and ground until the particle size is less than 1 μm to obtain an antibacterial dispersion.

[0047] (2) Terephthalic acid (PTA), ethylene glycol (EG), butanediol (BDO), and antimony trioxide are added to a reactor to make an alcohol-acid ratio of 1:1.2, wherein the mass fraction of butanediol (BDO) is 10%, and the amount of antimony trioxide added is 400ppm of the mass of the antibacterial low-melting-point slices. After beating for 20 minutes, three passes and three releases are performed; the reactor temperature is raised to 230°C, and the esterification stage is completed after the water is completely discharged. At the same time, an antibacterial dispersion is added to make the mass of zinc oxide in the antibacterial low-melting-point slices 10000ppm. After stirring at normal pressure for 30 minutes, liquid PEG2000 accounting for 3% of the mass of the antibacterial low-melting-point slices is added. After stirring for 15 minutes, vacuum is applied, and after 1 hour, the temperature is pumped to -0.1MPa. The temperature is controlled at 272°C. After a polycondensation reaction, the final antibacterial low-melting-point slices (with a characteristic viscosity of 0.71dl / g and a melting point of 180°C) are obtained.

[0048] (3) The antibacterial low melting point chips were pre-crystallized at a vacuum degree of -0.1 MPa and a temperature of 50°C for 4 h, and then dried in stages. The temperature was raised to 60°C for drying for 6 h, then raised to 70°C for drying for 6 h, and finally raised to 80°C for drying for 8 h, until the moisture content was below 20 ppm. The spinning process adopted a spinneret with a skin-core structure, in which the dried antibacterial low melting point chips were the skin layer and the conventional PET chips were the core layer, with a mass ratio of 30:70. The screw temperature of the skin spinning was 225°C / 230°C / 230°C / 230°C, and the spinning manifold temperature was 225°C. The screw temperature of the core spinning was 285°C / 290°C / 290°C / 290°C, and the spinning manifold temperature was 288°C.

[0049] The two melts form a fine flow at the core-sheath spinneret. The filament bundle formed after spinning is first cooled by side air blowing. The side air temperature is 20°C, the side air speed is 0.50m / s, and the side air humidity is 73%. Then it is oiled and stretched in sequence. The temperature of the first hot roller is 50°C, the temperature of the second hot roller is 100°C, and the stretching ratio is 3.0. Finally, it is wound at a speed of 3500m / min to obtain a low-melting-point antibacterial fiber with a core-sheath structure.

[0050] Comparative Example 2

[0051] The difference from Example 1 is that butanediol is replaced by an acid modifier (isophthalic acid).

[0052] (1) ZnO powder is dissolved in ethylene glycol twice its weight and stirred until there is no powder. The solution is then added to a grinder and ground. A polyvinyl pyrrole stabilizer accounting for 5% of the weight of the ZnO powder is added and ground until the particle size is less than 1 μm to obtain an antibacterial dispersion.

[0053] (2) Terephthalic acid (PTA), ethylene glycol (EG), and isophthalic acid are added to the reactor to make the alcohol-acid ratio of 1:1.2, wherein the molar ratio of isophthalic acid to alcohol to dibasic acid is 28%, and antibacterial dispersion and antimony trioxide are added at the same time, wherein the amount of antimony trioxide added is 400ppm of the mass of the antibacterial low-melting-point slices, and the mass of zinc oxide in the antibacterial low-melting-point slices is 10000ppm. After beating for 20 minutes, three passes and three releases are performed; the reactor temperature is raised to 230°C, and the esterification stage is completed after the water is completely discharged; then, after stirring at normal pressure for 20 minutes, liquid PEG2000 accounting for 3% of the mass of the antibacterial low-melting-point slices is added, and after stirring for 15 minutes, vacuum is applied, and after 1 hour, the vacuum is applied to -0.1MPa, and the temperature is controlled at 272°C. After a polycondensation reaction, the final antibacterial low-melting-point slices (with a characteristic viscosity of 0.70dl / g and a melting point of 180°C) are obtained.

[0054] (3) The antibacterial low melting point chips were pre-crystallized at a vacuum degree of -0.1 MPa and a temperature of 50°C for 4 h, and then dried in stages. The temperature was raised to 60°C for drying for 6 h, then raised to 70°C for drying for 6 h, and finally raised to 80°C for drying for 8 h, until the moisture content was below 20 ppm. The spinning process adopted a spinneret with a skin-core structure, in which the dried antibacterial low melting point chips were the skin layer and the conventional PET chips were the core layer, with a mass ratio of 30:70. The screw temperature of the skin spinning was 225°C / 230°C / 230°C / 230°C, and the spinning manifold temperature was 225°C. The screw temperature of the core spinning was 285°C / 290°C / 290°C / 290°C, and the spinning manifold temperature was 288°C.

[0055] The two melts form a fine flow at the core-sheath spinneret. The filament bundle formed after spinning is first cooled by side air blowing. The side air temperature is 20°C, the side air speed is 0.50m / s, and the side air humidity is 73%. Then it is oiled and stretched in sequence. The temperature of the first hot roller is 50°C, the temperature of the second hot roller is 100°C, and the stretching ratio is 3.0. Finally, it is wound at a speed of 3500m / min to obtain a low-melting-point antibacterial fiber with a core-sheath structure.

[0056] Comparative Example 3

[0057] The difference from Example 1 is that butanediol is replaced by an alcohol modifier (2,2-dimethyl-1,3-propanediol).

[0058] (1) ZnO powder is dissolved in ethylene glycol twice its weight and stirred until there is no powder. The solution is then added to a grinder and ground. A polyvinyl pyrrole stabilizer accounting for 5% of the weight of the ZnO powder is added and ground until the particle size is less than 1 μm to obtain an antibacterial dispersion.

[0059] (2) Terephthalic acid (PTA), ethylene glycol (EG), and 2,2-dimethyl-1,3-propylene glycol are added to the reaction kettle so that the alcohol-acid ratio is 1:1.2, wherein the mass fraction of 2,2-dimethyl-1,3-propylene glycol is 10%, and at the same time, antibacterial dispersion and antimony trioxide are added, wherein the amount of antimony trioxide added is 400ppm of the mass of the antibacterial low-melting-point slice, and the mass of zinc oxide in the antibacterial low-melting-point slice is 10000ppm. m, and then three passes and three releases were performed after beating for 20 minutes; the kettle temperature was raised to 230°C, and the esterification stage was ended after complete water discharge; then, liquid PEG2000 accounting for 3% of the weight of the antibacterial low-melting-point slices was added after stirring at normal pressure for 20 minutes, and vacuum was applied after stirring for 15 minutes. After 1 hour, the temperature was evacuated to -0.1 MPa, and the temperature was controlled at 272°C. After a condensation reaction, the final antibacterial low-melting-point slices (with a characteristic viscosity of 0.69 dl / g and a melting point of 180°C) were obtained.

[0060] (3) The antibacterial low melting point chips were pre-crystallized at a vacuum degree of -0.1 MPa and a temperature of 50°C for 4 h, and then dried in stages. The temperature was raised to 60°C for drying for 6 h, then raised to 70°C for drying for 6 h, and finally raised to 80°C for drying for 8 h, until the moisture content was below 20 ppm. The spinning process adopted a spinneret with a skin-core structure, in which the dried antibacterial low melting point chips were the skin layer and the conventional PET chips were the core layer, with a mass ratio of 30:70. The screw temperature of the skin spinning was 225°C / 230°C / 230°C / 230°C, and the spinning manifold temperature was 225°C. The screw temperature of the core spinning was 285°C / 290°C / 290°C / 290°C, and the spinning manifold temperature was 288°C.

[0061] The two melts form a fine flow at the core-sheath spinneret. The filament bundle formed after spinning is first cooled by side air blowing. The side air temperature is 20°C, the side air speed is 0.50m / s, and the side air humidity is 73%. Then it is oiled and stretched in sequence. The temperature of the first hot roller is 50°C, the temperature of the second hot roller is 100°C, and the stretching ratio is 3.0. Finally, it is wound at a speed of 3500m / min to obtain a low-melting-point antibacterial fiber with a core-sheath structure.

[0062] Table 1

[0063]

[0064] As shown in Table 1, the present invention adds zinc oxide nanoparticles during the low melting point polymerization process, so that the fiber has excellent antibacterial properties, and the antibacterial agent and the fiber matrix have good binding and compatibility, while improving the antibacterial property, the original performance advantages of the fiber are not damaged. Comparative Example 1 shows that the addition of zinc oxide antibacterial agent before esterification is more conducive to improving its compatibility and binding in the polyester molecular chain, and then the antibacterial and mechanical properties of the fiber are also good. Comparative Example 2 shows that butanediol, as a modified monomer in the polyester molecular chain, can not only reduce the melting point and improve the processability, but also can help the dispersion of zinc oxide and improve the antibacterial property by increasing the proportion of amorphous regions. While using isophthalic acid as a modified monomer, the spinnability of the resulting polyester is poor, and the original performance of the fiber is damaged. Comparative Example 3 shows that the polyester molecular chain structure that can be formed by using other alcohol modifiers (2,2-dimethyl-1,3-propanediol) relative to butanediol will be different, resulting in poor mechanical properties of the polyester fiber and affecting the proportion of the amorphous region, resulting in the antibacterial property not being effectively exerted.

[0065] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the specification of the present invention, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A method for preparing a low-melting-point antibacterial fiber based on zinc oxide particles, characterized in that: The steps include: (1) Add zinc oxide powder to ethylene glycol and stir thoroughly until there is no powder, then add a stabilizer and grind until the particle size is less than 1 μm to prepare an antibacterial dispersion; (2) terephthalic acid, ethylene glycol, butanediol, antibacterial dispersion and catalyst are mixed and slurried, and then heated to carry out esterification reaction; after the reaction is completed, PEG is added to carry out polycondensation reaction to obtain antibacterial low melting point slices; (3) The antibacterial low-melting-point chips were pre-crystallized at a vacuum degree of -0.1 MPa and a temperature of 50°C for 3 to 5 h, and then dried in sections. The chips were used as the skin layer and conventional PET chips were used as the core layer for melt spinning to obtain a low-melting-point antibacterial fiber with a skin-core structure.

2. The method for preparing low-melting-point antibacterial fiber based on zinc oxide particles according to claim 1, characterized in that: In step (1), the mass ratio of the zinc oxide powder to ethylene glycol is 1:2; the mass ratio of the stabilizer to the zinc oxide powder is 5:

100.

3. The method for preparing low-melting-point antibacterial fiber based on zinc oxide particles according to claim 1, characterized in that: In step (2), the alcohol-acid ratio of terephthalic acid, ethylene glycol and butanediol is 1:1.2-1.4, wherein the mass fraction of butanediol in alcohol is 10-12%.

4. The method for preparing low-melting-point antibacterial fiber based on zinc oxide particles according to claim 1, characterized in that: In step (2), the amount of the catalyst added is 350-500 ppm of the mass of the antibacterial low-melting-point slice; the mass of zinc oxide in the antibacterial low-melting-point slice is 4000-12000 ppm.

5. The method for preparing low-melting-point antibacterial fiber based on zinc oxide particles according to claim 1, characterized in that: In step (2), the molecular weight of the PEG is 2000-6000; the amount of the PEG added is 1-3% of the mass of the antibacterial low melting point slice.

6. The method for preparing low-melting-point antibacterial fiber based on zinc oxide particles according to claim 1, characterized in that: In step (2), the temperature of the esterification reaction is 220-240°C; the polycondensation reaction is: after vacuuming for 1 hour, the negative pressure is evacuated to -0.1 MPa, and the temperature is controlled to 270-275°C.

7. The method for preparing low-melting-point antibacterial fiber based on zinc oxide particles according to claim 1, characterized in that: In step (3), the staged drying is as follows: firstly heating to 60°C and drying for 5-7h, then heating to 70°C and drying for 5-7h, and finally heating to 80°C and drying for 8-9h, until the moisture content is below 20ppm.

8. The method for preparing low-melting-point antibacterial fiber based on zinc oxide particles according to claim 1, characterized in that: In step (3), during the melt spinning, the skin layer accounts for 30-40% of the total mass of the melt, the spinning manifold temperature of the skin layer is 225-227°C, and the spinning manifold temperature of the core layer is 288-290°C.

9. The method for preparing low-melting-point antibacterial fiber based on zinc oxide particles according to claim 1 or 8, characterized in that: In step (3), the filament bundle formed after melt spinning is sequentially subjected to side-blowing cooling, oiling, drawing, and winding to obtain a low-melting-point antibacterial fiber with a core-sheath structure.

10. The method for preparing low-melting-point antibacterial fiber based on zinc oxide particles according to claim 9, characterized in that: The temperature of the side blowing air is 20-25°C, the humidity is 70-75%, and the speed is 0.40-0.55 m / s; the temperature of the first hot roller for drawing is 40-55°C, the temperature of the second hot roller is 95-110°C, and the stretching ratio is 2.5-3.5; the winding speed is 3500-4000 m / min.

Citation Information

Patent Citations

  • Low-melting-point antibacterial specially-shaped polyester monofilament and processing method thereof

    CN105200550A

  • Low-melting point and high-crystallization temperature PET copolyester, its preparation method and application

    CN103102646A

  • Antibacterial DTY fiber and method for continuously producing antibacterial DTY fiber

    CN115637504A

  • KR20220103841A